2012
DOI: 10.1016/j.jacc.2012.08.977
|View full text |Cite
|
Sign up to set email alerts
|

New Unipolar Electrogram Criteria to Identify Irreversibility of Nonischemic Left Ventricular Cardiomyopathy

Abstract: Detailed unipolar voltage mapping can identify irreversible myocardial dysfunction consistent with fibrosis, even in the absence of bipolar EAM or cardiac magnetic resonance abnormalities, and may serve as valuable prognostic tool in patients presenting with LVCM to facilitate clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 13 publications
1
59
1
Order By: Relevance
“…This is in line with prior comparative studies, which showed that electroanatomic voltage mapping is significantly more sensitive than cardiac magnetic resonance to disclose areas of cardiomyopathic involvement. [39][40][41] This may be related to the inadequate spatial resolution of current magnetic resonance scanners especially for thin structures such as the right ventricular wall, with high risk of artifacts due to partial volume effect.…”
Section: Substrate Mapping: General Considerationsmentioning
confidence: 99%
“…This is in line with prior comparative studies, which showed that electroanatomic voltage mapping is significantly more sensitive than cardiac magnetic resonance to disclose areas of cardiomyopathic involvement. [39][40][41] This may be related to the inadequate spatial resolution of current magnetic resonance scanners especially for thin structures such as the right ventricular wall, with high risk of artifacts due to partial volume effect.…”
Section: Substrate Mapping: General Considerationsmentioning
confidence: 99%
“…Interestingly, there was a strong correlation between parameters of RV function and viability of IVS, suggesting that ventricular interdependence may at least partially account for the observed changes 15, 16. Previously it has been demonstrated that measurement of endocardial UV can be used to identify left ventricular dysfunction in the absence of macroscopic scar defined with standard cardiac magnetic resonance imaging (cMRI) criteria, which suggests that unipolar electrograms could also detect a more diffuse underlying myocardial process 17. Moreover, an inverse relation between amplitude of unipolar endocardial recordings and myocardial fibrosis burden has been described already in an experimental model of nonischemic cardiomyopathy and in an anatomic study of explanted human hearts 18, 19.…”
Section: Discussionmentioning
confidence: 98%
“…6,7,15 Further, unipolar voltage by EMM has been shown to identify areas of myocardial fibrosis and possibly to help identify suitable targets for cell therapy 16 and therapeutic angiogenesis. 17 That EMM's identification of viable myocardial tissue as a target in ischemic cardiomyopathy patients can be used to maximize the effects of cell therapy is still hypothetical, however.…”
Section: Were Engaged By Needle and Injected (With Bmc Or Placebo)mentioning
confidence: 99%